Kalilo river pollution due to limited land settlement and human behavior along the Kalilo riverbanks - Suprihatin, H (Brawijaya University, 2014)
Kalilo River is one of the sights that is always visible to the people who come cross to Banyuwangi. However, there are many trash and animal (human) defecation in the Kalilo river that mayÂ impair the beautiful scenery of the river. This study was aimed to measure whether or not the physical, chemical and bacteriological parameters of the river water meets the criteria of Class II Water Quality Standard. River water samples were collected from upstream, midstream and downstream of the Kalilo river for suspended solid, sulfate, total phosphate, BOD, COD, DO, anionic detergent, total coliforms. Results of water analysis showed that the suspended solid, sulfate, total phosphate, BOD, COD, DO, anionic detergent, total coliform contents exceeded standard limit of the of Class II Water Quality Standard. Such conditions affect physical, environmental and economic development of the district. A Communal Waste Treatment Plant, Anaerobic Baffle Reactor (ABR), is recommended to overcome the problems.